Theory of particle swarm optimization: A survey of the power of the swarm’s potential - Bassimir, Bernd; Raß, Alexander; Schmitt, Manuel (it - Information Technology, 2019)
This paper presents a survey on different showcases for potential measures on particle swarm optimization (PSO). First, a potential is analyzed to prove convergence to non-optimal points. Second, one can apply a minor modification to PSO to prevent convergence to non-optimal points by using an easy potential measure. Finally, analyzing this potential measure yields a reliable stopping criterion for the modified PS
Keywords: Particle swarm optimization; potential; meta-heuristics